A SYSTEMATIC REVIEW OF THE ASSOCIATION BETWEEN ADIPOSITY AND SPORT INJURY RISK IN YOUTH. Issue 4 (1st February 2017) - Toomey, Clodagh; Patton, Declan; Whittaker, Jackie; Richmond, Sarah; Emery, Carolyn
Abstract : Background: Obesity, defined as an accumulation of excessive fat mass that impairs health, is associated with lower levels of neuromuscular control including balance and coordination, which may place youth with higher adiposity at greater risk for injury during sport participation. On the opposite end of the spectrum, excessively low fat mass can also pose an injury risk. Objective: To determine if adiposity is a risk factor for sport injury in children and adolescents. Design: Systematic Review. Methods: Ten electronic databases were systematically searched using key words and Medical Sub-Heading terms. Studies selected included: English language; original data; analytic design; adiposity measurement by age- and sex-adjusted body mass index (BMI) or body fat using imaging, impedance or predictive methods and; children, adolescents and young adults ≤20 years who sustained a musculoskeletal injury during sport or recreation participation that resulted in medical attention or time loss from sport or activities. PRISMA guidelines were followed and studies were assessed by two independent raters. Level of evidence was assessed using the Oxford Centre of Evidence-Based Medicine model. Results: Of 8029 potentially relevant records, 44 were included in the final review. 75% of these studies were of prospective cohort design (level 2b evidence). Twenty-one studies concluded that a BMI rating of overweight/obese is a significant risk factor for injury; the majority (12/21) of these studies assessed lower extremity injury (e.g. ankle sprain and medial tibial stress syndrome). Nineteen studies showed no association between anthropometric measurement and injury; the majority (14/19) assessed all sport injury. Finally, a BMI rating of underweight (4 studies) was more commonly associated with risk of stress fracture. Conclusions: There is consistent level 2b evidence that a rating of overweight/obesity is associated with lower extremity injury. Anthropometric risk of injury appears to be dependent on type and site of injury in youth sport.